The Mushar District in the 16th Century - Çakar, Enver (Fırat University, 2020)
Mushar known as Minşar and Masara in the Middle Ages is a castle located on the banks of the Euphrates River. The district (nahiya) of Mushar, named after this castle, was bound to the Sanjaq of Malatya in the 16th century. There was a boat (kelek) in Ataf, one of the villages that made up the district, and a ship management in Rabat. River transportation between the two sides of the Euphrates was also carried out by the ships and boats (kelks) in these villages. Therefore, Mushar was located on the connection points of the roads from Malatya to Harput and Keban, and from there to Diyarbakır and Erzincan. The castle, which gave its name to the district, was an important garrison controlling the passages between both sides of the river.There were 15 villages and 23 hamlets in 1530 and 16 villages and 25 hamlets in 1560 in Mushar district. The most important livelihood of the villages was agriculture and animal husbandry. Half of the tax revenues obtained from villages and hamlets were assigned to foundations and properties as malikâne in 1530, and the other half as private or timar with the name of divani. Again, the rüsûm-ı örfiye was collected by the state or its representatives. However, in 1560 most of the malikâne shares were also seized on behalf of the state.The villages of Mushar district differed in terms of population density. Villages with businesses such as dyehouse, ship and scaffolding, and villages with lodges were settlements that were crowded in terms of population. In this respect, Ataf, Berete, Rabat and Şeyh Hasanlu villages were more developed than other villages.In this study, the administrative structure of Mushar District, population and economic resources of the villages, foundations and properties were examined in the light of the sanjaq of Malatya tahrir registers.

Muşar, Fırat Nehri kıyısında yer alan ve Ortaçağlarda Minşar ve Masara adlarıyla bilinen bir kaledir. Bu kaleden adını alan Muşar Nahiyesi 16. yüzyılda Malatya Sancağı’na bağlıydı. Nahiyeyi oluşturan köylerden Ataf’ta kelek, Rabat’ta ise gemi işletmesi vardı. Fırat’ın iki yakası arasındaki nehir taşımacılığı da bu köylerdeki gemi ve kelekler vasıtasıyla yapılmaktaydı. Dolayısıyla Muşar, Malatya’dan Harput ve Keban’a, oralardan da Diyarbakır ve Erzincan’a ulaşan yolların bağlantı noktaları üzerinde yer alıyordu. Nahiyeye adını veren kale ise nehrin her iki yakası arasındaki geçişleri denetleyen önemli bir garnizon görevini üstlenmişti. Muşar Nahiyesi’nde 1530’da 16 köy ve 22 mezra, 1560’ta ise 16 köy ve 25 mezra bulunmaktaydı. Köylerin en önemli geçim kaynağı tarım ve hayvancılıktı. Köy ve mezralardan sağlanan vergi gelirlerinin yarısı 1530’da malikâne adıyla vakıf ve mülklere, diğer yarısı da divanî adıyla has veya tımar olarak tevcih edilmişti. Yine rüsum-ı örfiyesi de devlet veya temsilcileri tarafından toplanıyordu. Fakat 1560’ta çoğu malikâne hisselerine de devlet adına el konulmuştur. Muşar Nahiyesi köyleri nüfus yoğunluğu bakımından farklılıklar gösteriyordu. Boyahane, gemi ve kelek gibi işletmelere sahip olan köyler ile zaviyesi olan köyler nüfus bakımından kalabalık olan yerleşmelerdi. Bu açıdan Ataf, Berete, Rabat ve Şeyh Hasanlu köyleri diğer köylere nazaran daha fazla gelişmişti. Bu çalışmada Malatya Sancağı tahrir defterleri ışığında Muşar Nahiyesi’nin idarî yapısı, köylerinin nüfusu ve ekonomik kaynakları ile vakıf ve mülkleri incelenmiştir.
16. Yüzyılda Muşar Nahiyesi